2017
DOI: 10.1111/emre.12134
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Environmental Management: Individual‐Level Drivers and the Moderating Role of Charismatic Leadership

Abstract: Drawing upon norm‐activation and social cognitive theories, we examine whether the personal norms and self‐efficacy of top managers affect their decisions to engage in environmental management initiatives (EMI). We also investigate whether this relationship is moderated by CEO charisma. Empirical evidence from a sample of 125 companies indicates that significant variation in EMI is explained by the two activators of personal norms – namely, awareness of consequences and ascription of responsibility – as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 95 publications
(149 reference statements)
3
29
0
Order By: Relevance
“…In good agreement with Doluca, Holzner, and Wagner (2018), our findings reveal a positive development of corporate sustainability Our results thus support earlier findings by Zhang et al (2013) and Papagiannakis and Lioukas (2017), who found for the context of employees within corporations that actions concerning an issue lead to higher levels of awareness about this issue and sensitise for the sustainability-related consequences of the corporations' actions. Our analysis furthermore reveals that the positive effect of corporate action on awareness for sustainability-related consequences is positively moderated by feedback.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In good agreement with Doluca, Holzner, and Wagner (2018), our findings reveal a positive development of corporate sustainability Our results thus support earlier findings by Zhang et al (2013) and Papagiannakis and Lioukas (2017), who found for the context of employees within corporations that actions concerning an issue lead to higher levels of awareness about this issue and sensitise for the sustainability-related consequences of the corporations' actions. Our analysis furthermore reveals that the positive effect of corporate action on awareness for sustainability-related consequences is positively moderated by feedback.…”
Section: Discussionsupporting
confidence: 92%
“…For the context of this paper, this implies that corporations become aware of the importance of the environment and social issues for them through engaging in corporate sustainability and consequently further improve their sustainability‐related actions. This finding lends support to Papagiannakis and Lioukas (), who also reported a positive influence of awareness of consequences of managers in Greek manufacturing companies on their engagement in corporate sustainability actions. The results are also in line with the findings by Qian and Schaltegger (), who found that improving disclosure on carbon information leads to improved carbon performance in subsequent periods of time.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations